2016
DOI: 10.3390/ijms17081264
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Digital PCR Based Androgen Receptor Variant 7 (AR-V7) Detection from Prostate Cancer Patient Blood Biopsies

Abstract: Androgen receptor splice variant V7 (AR-V7) was recently identified as a valuable predictive biomarker in metastatic castrate-resistant prostate cancer. Here, we report a new, sensitive and accurate screen for AR-V7 mRNA expression directly from circulating tumor cells (CTCs): We combined EpCAM-based immunomagnetic CTC isolation using the IsoFlux microfluidic platform with droplet digital polymerase chain reaction (ddPCR) to analyze total AR and AR-V7 expression from prostate cancer patients CTCs. We demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 31 publications
6
54
1
Order By: Relevance
“…In total, 252 VCaP, 108 LNCap, and 186 PC-3 cells were evaluated and RCPs quantified by CellProfiler software. The in situ results reflect previously published data (22 ). VCaP cells seeded onto the CellCollector showed results comparable with cells on a slide (Fig.…”
Section: Ar-v7 Ar-fl and Psa Can Be Visualized And Quantified In Prsupporting
confidence: 90%
See 1 more Smart Citation
“…In total, 252 VCaP, 108 LNCap, and 186 PC-3 cells were evaluated and RCPs quantified by CellProfiler software. The in situ results reflect previously published data (22 ). VCaP cells seeded onto the CellCollector showed results comparable with cells on a slide (Fig.…”
Section: Ar-v7 Ar-fl and Psa Can Be Visualized And Quantified In Prsupporting
confidence: 90%
“…1). The terms positive and negative refer to previously published data as detectable and not detectable mRNA, respectively (22 ). For VCaP cells, the average numbers of RCPs/ cell for AR-V7, AR-FL, and PSA were 3.2 (range, 0 -20), 2.7 (range, 0 -19), and 0.6 (range, 0 -7), respectively.…”
Section: Ar-v7 Ar-fl and Psa Can Be Visualized And Quantified In Prmentioning
confidence: 99%
“…Additionally, the detection of mRNA confirms that cells remain intact in the blood sample as it is well established that any released free RNA will be quickly degraded by RNases in the blood [27]. Since cultured 22Rv1 cells are potentially more robust and survive extended storage in blood samples better than CTCs, we confirmed that AR-V7 detection after 48 h storage was translatable to patient CTC samples by testing three patients previously shown to have high CTC AR-V7 expression [7]. Although a small decrease in AR-V7 levels after 48 h was detected in these patient samples, the decrease was marginal in this time frame and even in patient blood with low AR-V7, CTC derived AR-V7 was still detectable after 48 h blood storage at room temperature.…”
Section: Discussionsupporting
confidence: 69%
“…Several different blood-based AR-V7 detection assays are available, including CTC-based protein immunofluorescence and mRNA-based assays that can be performed using CTCs, whole-blood RNA, and plasma-derived exosomes [16,20]. Furthermore, different detection technologies are [11][12][13][14][15][21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%